A Latent Profile Analysis of Romantic Relationship Quality and Its Associations with Personality, Partner Support, and Psychological Well-Being - Chen, Samantha (2015)
The current study investigated the number of relationship quality profiles that emerge from a latent profile analysis and subsequently examined the nature of each subgroup using predictors of partner social support and personality, as well as outcomes of psychological well-being. The application of latent profile analysis resulted in three profiles of low, moderate, and high relationship quality among a sample of university students. Additionally, predictors and outcomes of profile membership were incorporated to provide a greater descriptive understanding of the latent profiles. Results showed that the relationship between intimacy and passion and the relationship between relationship satisfaction and received esteem support were positively associated across all three profiles of relationship quality. In contrast, relationships of high quality generally show a greater number of intercorrelations among important relationship quality components, and are associated with lower levels of negative supportive behaviours. Furthermore, perceived partner support, emotional support, esteem support, and honesty-humility were significant predictors that distinguished between the profiles. Lastly, individuals in high quality relationships reported more positive and less negative psychological outcomes, which showed significant associations with relationship satisfaction and trust. Overall, the present study presents a novel use of a person-centred approach to the understanding of relationship quality